The Search for Exit Strategies from Neo-Colonial Interventions - Pearson, Frederic; Lounsbery, Marie; Costa, Loreta (Journal of Conflict Studies, 2005)
ABSTRACT In many respects the current US situation in Iraq is one that resembles a colonial or neo-colonial policy. This involves forced entry by external great powers bent on reshaping the political system and taking command of the economic resources and their use. Although the initial conflict was international in nature, a persistent insurgency continues to challenge these efforts. The United States, nonetheless, continues to work toward a successful withdrawal from Iraq. This article explores the potential for successful exit. Using a case set of 17 extra-state wars for the period 1945-99, the authors explore factors of international support, exit agreements, and additional conflict variables in relation to exit outcome. Although a clear pattern of successful exit does not emerge, our findings sug gest that some of our assumptions regarding newly emerging states and external power withdrawal should perhaps be questioned.